Systematic Literature Review: The Paradigm Of Developing Nations Oriented Towards Falah - Anggara, Windu; Harahap, Isnaini; M. Nawawi, Zuhrinal (Publisher Cv. Inara, 2024)
This systematic literature review delves into the emerging paradigm witnessed in developing nations as they shift their development strategies towards the concept of Falah. Rooted in Islamic principles, Falah encapsulates holistic well-being, prosperity, and the fulfillment of societal needs. The review synthesizes diverse scholarly articles, research papers, and academic contributions to explore the theoretical foundations, policy implications, and practical applications of the Falah-oriented development approach across developing nations. Highlighting the experiences of countries such as Malaysia, Indonesia, Pakistan, Bangladesh, and Saudi Arabia, the study underscores the transformative role of Falah in shaping economic development strategies. From the integration of Falah-based economies to the empowerment of Sharia-compliant economic sectors, each nation exhibits a unique approach to realizing this paradigm. The article emphasizes the significance of aligning with Sharia principles, fostering socio-economic well-being, and contributing to sustainable development goals. The findings illuminate the pivotal role of Falah as a catalyst for positive change, offering valuable insights into alternative development paradigms and their potential contributions to holistic well-being and sustainable development in the developing world.